The effect of Inquiry-Based Physics E-LKPD on interests and learning outcomes of High School students in Bandar Lampung City - E. Erni; H. Herpratiwi; H. Handoko (Inovasi Kurikulum, 2023)
The learning outcomes for the Physics Subject in Bandar Lampung City are low. In addition, the Physics Subject is also not popular among students, especially at the high school level in Bandar Lampung City. To overcome these problems, teachers need to do innovative learning. This study aimed to produce an inquiry-based Physics E-LKPD, which experts validated, and to analyze the effect of the product on learning interest and learning outcomes for Physics in SMA in Bandar Lampung City. Research is a development study with a research population of 17 High Schools in Bandar Lampung City. The school sample was taken using a stratified random sampling technique, while the student samples were taken using a proportional stratified method. Product data was collected through interviews, observation, questionnaires, and validation of material, design, and media experts. In contrast, data on learning outcomes and interest in learning the field of physics studies were taken from documentation and questionnaires. The effect of using guided inquiry-based E-LKPD was analyzed by t-test. The study results illustrate that the development of guided inquiry-based E-LKPD has met the valid and practical criteria for learning physics in high school, especially the solar system. The E-LKPD was developed through defining, designing, and developing. Based on these results, it can be concluded that guided inquiry-based E-LKPD positively impacts learning outcomes and student learning interests. AbstrakHasil belajar untuk Mata Pelajaran Fisika di Kota Bandar Lampung tergolong rendah. Selain itu Mata Pelajaran Fisika juga tidak populer di kalangan peserta didik khususnya di jenjang SMA di Kota Bandar Lampung. Untuk mengatasi permasalahan tersebut, maka guru perlu melakukan pembelajaran yang inovatif. Tujuan penelitian ini untuk menghasilkan E-LKPD Fisika berbasis inkuiri yang divalidasi oleh pakar dan untuk menganalisis pengaruh produk terhadap minat belajar dan hasil belajar Mata Pelajaran Fisika pada SMA di Kota Bandar Lampung. Penelitian-merupakan penelitian pengembangan dengan populasi penelitian adalah 17 SMAN di Kota Bandar Lampung. Pengambilan sampel sekolah dilakukan dengan teknik strataified random sampling, sedangkan untuk sampel peserta didik dengan probability sampling teknik propotional stratified. Pengumpulan data untuk produk dilakukan melalui wawancara, observasi, angket, validasi ahli materi, ahli desain, dan ahli media, sedangkan untuk data hasil belajar dan minat belajar bidang studi Fisika diambil dari dokumentasi serta angket. Pengaruh penggunaan E-LKPD berbasis inkuiri terbimbing dianalisis dengan t-test. Hasil penelitian menggambarkan bahwa pengembangan E-LKPD berbasis inkuiri terbimbing telah memenuhi kriteria valid dan efektif dalam pembelajaran Fisika di SMA, terutama tata surya. E-LKPD tersebut dikembangkan melalui tiga tahap, yaitu pendefinisian (define), perancangan (design), dan pengembangan (development). Berdasarkan hasil tersebut dapat disimpulkan bahwa penggunaan E-LKPD berbasis inkuiri terbimbing memiliki dampak positif dalam meningkatkan hasil belajar dan minat belajar peserta didik.Kata Kunci: E-LKPD Fisika; inkuiri; minat belajar; hasil belajar